Does delaying surgery help, hurt or make no difference with an athlete`s return to play after ACL rupture? - Baur, J. A. (Physical Therapy First, 2020)
Frobell et al BMJ 2013 findings in a 5-year report shows that there was no difference in any outcome between those who were operated on straight away, those who were operated on later and those who did not have an operation at all. The message to the medical experts who are treating young, active patients with ACL injuries is that it may be better to start by considering physical therapy first rather than operating right away.